Why Teachers Stay: Shaping a New Narrative on Rural Teacher Retention - Jennifer L. Seelig; Katie M. McCabe (Journal of Research in Rural Education, 2021)
Teacher retention studies often focus on why teachers leave the profession, but this article suggests that focusing on why teachers stay situates rural school and community assets as the foundation to reform. The research design is a collective case study of three rural Wisconsin school districts, and findings are based on interviews and focus groups with 44 teachers and six administrators. Our study's findings reveal the centrality of relationships to teachers' decisions to stay in their rural schools. We present four relationship categories: (a) commitment to students, (b) opportunities for leadership and collaboration, (c) connections to community, and (d) personal and professional ties. Our study suggests the need for a conceptual reframing, or a new way of thinking, in research on teacher retention. Practical implications for addressing rural teacher retention are also surfaced, suggesting a new way of "doing" that situates school-community relationships at the center.